Spatial and Temporal Variation of Physico-chemical Parameters in the Merbok Estuary, Kedah, Malaysia - Kaniz Fatema; Wan Maznah W O; Mansor Mat Isa (Tropical Life Sciences Research, 2014)
In this study, factor analysis (FA) was applied to extract the hidden factors responsible for water quality variations during both wet and dry seasons. Water samples were collected from six sampling stations (St. 1 Lalang River, St. 2 Semeling River, St. 3 Jagung River, St. 4 Teluk Wang River, St. 5 Gelam River and St. 6 Derhaka River) in the Merbok estuary, Malaysia from January to December 2011; the samples were further analysed in the laboratory. Correlation analysis of the data sets showed strong correlations between the parameters. Nutrients such as nitrate (NO3–), nitrite (NO2–), ammonia (NH3) and phosphate (PO43–) were determined to be critical indicators of water quality throughout the year. Influential water quality parameters during the wet season were conductivity, salinity, biochemical oxygen demand (BOD), dissolved oxygen (DO) and chlorophyll a (Chla), whereas total suspended solid (TSS) and pH were critical water quality indicators during the dry season. The Kruskal-Wallis H test showed that water quality parameters were significantly different among the sampling months and stations (p<0.05), and Mann-Whitney U tests further revealed that the significantly different parameters were temperature, pH, DO, TSS, NO2– and BOD (p<0.01), whereas salinity, conductivity, NO3–, PO43–, NH3 and Chla were not significantly different (p>0.05). Water quality parameters in the estuary varied on both temporal and spatial scales and these results may serve as baseline information for estuary management, specifically for the Merbok estuary. Dalam kajian ini, analisis faktor (FA) telah digunakan untuk mendapatkan faktor-faktor tersembunyi yang bertanggungjawab untuk variasi kualiti air dalam kedua-dua musim hujan dan panas. Sampel air diambil dari enam stesen persampelan (St. 1 Sungai Lalang, St. 2 Sungai Semeling, St. 3 Sungai Jagung, St. 4 Sungai Teluk Wang, St. 5 Sungai Gelam dan St. 6 Sungai Derhaka) di muara Merbok, Malaysia dari Januari hingga Disember 2011; sampel telah dianalisis selanjutnya di makmal. Analisis korelasi daripada set data menunjukkan korelasi yang kuat antara parameter. Nutrien seperti nitrat (NO3–), nitrit (NO2–), ammonia (NH3) dan fosfat (PO43–) menjadi petunjuk penting kualiti air sepanjang tahun. Parameter kualiti air yang mempengaruhi semasa musim hujan ialah kekonduksian, kemasinan, keperluan oksigen biokimia (BOD), oksigen terlarut (DO) dan klorofil a (Chla), manakala pepejal terampai total (TSS) dan pH merupakan indikator kualiti air penting pada musim kemarau. Ujian Kruskal-Wallis H menunjukkan bahawa parameter kualiti air berbeza dengan signifikan antara bulan-bulan persampelan dan stesen (p<0.05), dan ujian Mann-Whitney U seterusnya mendedahkan parameter yang berbeza dengan signifikan adalah suhu, pH, DO, TSS, NO2– dan BOD (p<0.01), manakala kemasinan, konduktiviti, NO3–, PO43–, NH3 dan Chla tidak berbeza secara signifikan (p>0.05). Parameter kualiti air di muara ini bervariasi secara temporal dan spatial, dan keputusan ini dapat berfungsi sebagai maklumat garis asas untuk pengurusan muara, khususnya untuk muara Merbok.